TRANSMISSION COMPUTATIONAL MODEL IN SIMULINK (Perner's Contacts, 2013)
The article describes the creation of a transmission and a clutch computational model. These parts of the powertrain are created using basic blocks from the Simulink library, with the input values obtained from the manufacturer. The description of a computational model and its setup in Simulink software is presented in this article. In the end, the evaluation of two simulations of gear shifting and running the transmission on the dynamometer is discussed.